2020
DOI: 10.1088/1741-4326/ab9884
|View full text |Cite
|
Sign up to set email alerts
|

Pedestal dynamics prior to type-III ELM onset on HL-2A tokamak*

Abstract: A dramatic increase of density gradient and a slight decrease of electron temperature gradient were observed in the pedestal just prior to each onset in a series of ELM bursts. An inward particle flux induced by a quasi-coherent mode was found to be responsible for such changes. The characteristics of the quasi-coherent mode, including frequency, wave vector, propagation direction and velocity were identified. The nonlinear three-wave coupling is a plausible mechanism for the generation of the mode. Decoupling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…The impurity experiments were performed in ohmicallyheated deuterium plasmas on the HL-2A tokamak (a/R = 0.4 m/1.65 m) with the limiter configuration under the following discharge parameters: plasma current I p ≈ 190 kA, line-averaged density n el ≈ 2 × 10 19 m −3 , toroidal magnetic field B t ≈ 1.5 T, edge safety factor q ∼ 3.6 and edge ion-ion collisionality v ii ≈ 3-5 kHz. Recently, zonal flow [16], the energy transfer rate [17], limit-cycle oscillations [18][19][20], pedestal instability [21] and the divertor particle flux [22] have been actively studied in the HL-2A tokamak with multiple Langmuir probe arrays [23]. Figure 1(a) depicts the arrangement of the stationary Langmuir probe at point A and the reciprocating system at point B, both located at the outer mid-plane in the HL-2A tokamak.…”
Section: Methodsmentioning
confidence: 99%
“…The impurity experiments were performed in ohmicallyheated deuterium plasmas on the HL-2A tokamak (a/R = 0.4 m/1.65 m) with the limiter configuration under the following discharge parameters: plasma current I p ≈ 190 kA, line-averaged density n el ≈ 2 × 10 19 m −3 , toroidal magnetic field B t ≈ 1.5 T, edge safety factor q ∼ 3.6 and edge ion-ion collisionality v ii ≈ 3-5 kHz. Recently, zonal flow [16], the energy transfer rate [17], limit-cycle oscillations [18][19][20], pedestal instability [21] and the divertor particle flux [22] have been actively studied in the HL-2A tokamak with multiple Langmuir probe arrays [23]. Figure 1(a) depicts the arrangement of the stationary Langmuir probe at point A and the reciprocating system at point B, both located at the outer mid-plane in the HL-2A tokamak.…”
Section: Methodsmentioning
confidence: 99%
“…For example, the Type-III ELM regime has traditionally been associated with the resistive-ballooning mode. Recently, experimental analysis on the HL-IIA tokamak [44][45] has demonstrated that streamers develop in the plasma core during the internal energy collapse phase, corresponding to the onset of Type-III ELMs. These results are consistent with large-scale nonlinear simulations indicating the existence of unexpected and distinct physical mechanisms for Type-III ELMs.…”
Section: Comparison With Previous Workmentioning
confidence: 99%
“…The bispectral analysis technique [33] has been widely used to study the nonlinear coupling in several experiments [34][35][36]. The squared auto-bicoherence is defined as b It is clearly shown that the bicoherence values along the f 2 = ±11.7 kHz and f 2 = − f 1 ± 11.7 kHz lines in the case with tungsten ions are much larger than those without tungsten injection, indicating that the nonlinear coupling of fluctuations is significantly enhanced with tungsten injection.…”
Section: Evidence For the Enhanced Interaction Of Gam And Turbulencementioning
confidence: 99%